Pengembangan Media Flashcard Berbasis Metode Fonik dalam Meningkatkan Kemampuan Dekoding Siswa Kelas 1 Sekolah Dasar - Maria Goreti Rini Kristiantari; Chindytia; Ni Ketut Mas Ayu Marini Putri; Ni Kadek Subening Metia Putri; Lady Ayu Dhyana Paramita (Indonesian Gender and Society Journal, 2025)
The low ability of first grade elementary school students in recognizing letters and associating them with the right sounds indicates the need for effective media and learning methods to support mastery of decoding skills at the early stages of reading. This study aims to create media flash card based on phonics methods in improving students' decoding abilities and assessing the extent to which flashcard media based on phonics methods can improve students' abilities in recognizing letter sounds and combining them into words. The research method used is qualitative and quantitative descriptive analysis, with data collection through observation, interviews, and questionnaires. This study uses the ADDIE development model as a framework in designing and developing media. The research subjects consisted of 9 grade 1 elementary school students, as individual trial subjects. The main results of the study showed that the media obtained a very good category from design and media experts, and good from the results of individual trials. The media was considered interesting, easy to use, and helped students in mastering basic phonics. All of the 9 students have also experienced an increase in their early reading skills after using the media. It can be concluded that the media flash card based on phonics method contributes positively to improving students' early reading skills, especially in the aspect of decoding letters and words. The implications of this study indicate that the use of interactive visual media that is in accordance with phonics principles can effectively help students in recognizing the relationship between letters and sounds. This has an impact on improving basic reading skills, especially in terms of decoding or the ability to sound out words accurately.